Using technology to sell : tactics to ratchet up results - London, Jonathan; Lucas, Martin, 1977- (Apress ; Distributed to the Book trade worldwide by Springer-Verlag New York, 2012)
"Shows salespeople and sales managers the most effective ways to leverage a variety of technologies to increase sales and gain more customers. Topics include making the most of cloud-based customer relationship management software, putting social media to the best use, presenting to customers worldwide through video conferencing, using advanced techniques like video "white papers" to differentiate your product or service, and gaining an information edge over competitors through alerts and other means"--Back cover